Can coarse‐grain patterns in insect atlas data predict local occupancy?. Issue 8 (29th March 2014) - Barwell, Louise J.; Azaele, Sandro; Kunin, William E.; Isaac, Nick J. B.; Richardson, David
Abstract Aim Species atlases provide an economical way to collect data with national coverage, but are typically too coarse‐grained to monitor fine‐grain patterns in rarity, distribution and abundance. We test the performance of ten downscaling models in extrapolating occupancy across two orders of magnitude. To provide a greater challenge to downscaling models, we extend previous downscaling tests with plants to highly mobile insect taxa (Odonata) with a life history that is tied to freshwater bodies for reproduction. We investigate the species‐level correlates of predictive accuracy for the best performing model to understand whether traits driving spatial structure can cause interspecific variation in downscaling success. Location Mainland Britain. Methods Occupancy data for 38 British Odonata species were extracted from the Dragonfly Recording Network (DRN). Occupancy at grains ≥ 100 km2 was used as training data to parameterize ten downscaling models. Predicted occupancy at the 25, 4 and 1 km2 grains was compared to observed data at corresponding grains. Model predictive error was evaluated across species and grains. Main conclusions The Hui model gave the most accurate downscaling predictions across 114 species:grain combinations and the best predictions for 14 of the 38 species, despite being the only model using information at a single spatial grain. The occupancy–area relationship was sigmoidal in shape for most species. Species' distribution type and dispersal ability explained over half of the variation in downscaling predictive error at the species level. Species with a climatic range limit in Britain were poorly predicted compared with other distribution types, and high dispersal ability was associated with relatively poor downscaling predictions. Our results suggest that downscaling models, using widely available coarse‐grain atlas data, provide reasonable estimates of fine‐grain occupancy, even for insect taxa with strong spatial structure. Linking species‐level traits with predictive accuracy reveals general principles about when downscaling will be successful.